Spoznavanje sevniške kulture in kulinarike s kolesom - Potočnik Topler, Jasna; Lisec, Andrej (2018)
Familiarizing with the Culture and Culinary of Sevnica by Bicycle. The monograph tackles the issue of exploring the culture and culinary of Sevnica by bicycle, and brings some project solutions. The goal of the students’ innovative project was to create a bicycle route through the municipality of Sevnica. The route had to be appropriate for families with young children and for immigrant families as well. It was decided to do two cycling paths, which are parts of one route. It was also decided to present the history through the wheelwrights that used to make waggons. The students also connected paths to baron Moscon that used to live in the Sevnica castle. To also include present and not only history students added the American First Lady. The first path was named Ursa Minor after the smaller constellation and it is 16.5 km long. It covers seven destinations with natural and cultural attractions, and with the providers of the local foods and drinks. The second path was named Ursa Major after the bigger constellation and it is 34.8 km long. To make the route more attractive and interesting for kids, we added stories, which were also made interactive by including stamps that kids collect at each attraction.
Keywords: Bicycle tourism; Sevnica; tourism Sevnica; storytelling; Slovenia